ANALISIS PERBANDINGAN PEREKONOMIAN PADA EMPAT KORIDOR DI PROPINSI JAWA TIMUR - Zainal . Arifin (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
The purpose of this study is to identify how the pattern of economic growth at the district level in each of the corridors in the province of East Java; identify what sectors could be developed in an effort to determine development priorities at the district level in each corridor in East Java Province, and to compare the level of the economy on four corridors in East Java Province. Based on comparative analysis of the economy can be explained that the North South Corridor has on the economy ranked first, followed by Southwest corridor, then the Eastern Corridor and the final ranking of the North Corridor